THE RELATIONSHIP BETWEEN SOCIAL ECOLOGY AND THE CONCEPT OF SUSTAINABLE DEVELOPMENT (Innovate Conferences, 2025)
This article analyzes the interrelationship between social ecology and the concept of sustainable development. It highlights the preservation of balance between humans and nature, the formation of ecological awareness and culture, and the dialectical connection between social and ecological systems of society. The concept of sustainable development is interpreted as the practical outcome of social ecology.